L'Élevage des vers à soie au Cambodge - Bernard Dupaigne (Revue d'ethnoécologie)
Silkworm breading has been studied in Cambodian villages by the author from 1968 to 1970. The present paper provides an extensive description of the craft, from cocoons to silk threads, as well as the economic context, at that time. Summary of the actual situation of silk production is also provided.